Sediment Assessment of Al-Hindyia and Al-Abbasyia River / Iraq by aquatic oligocheata community as bioindicators (Baghdad Science Journal, 2023)
Bioindicators have an important role in assessing the quality of water bodies. Aquatic oligocheates, was used as a bioindicator to assess the sediment quality of Al-Hindyia and AL-Abbasyia river (branches of Euphrates River in Iraq). Two sites in each river have been   chosen for this purpose, site S1 was located at Al-Hindyia River and S2 at Al-Abbasyia River. Some kinds of biological indices were used in this study, comprising the percentage of oligochaetes in benthic invertebrates, ranged from 20.3-60.16%. While the percentage of Tubificidae within benthic invertebrates was close 43.3-43.9%.Index of pollution D ranged from 0.13-0.21. The maximum percentage of aquatic oligochaetes to insects larvae of family Chironomidae larvae was recorded at S2 90% while at S1 60%. I0 was scored high value at S1 36.06 whilst only 30.56 at S2.E0 was A8 at S1 and A9 at S2.while IOBS was 15.26 at S2 and 7.07 at S1.The percentage of subfamily Tubificidae (TUSP) showed the highest value 21.21% at S1 while 11.79%at S2 .